Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.9790/3008-09355964
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan induces Apoptosis in MDA-MB-231 Cells by Activating Caspase Cascade and Down-regulating XIAP

Abstract: Summary: Previous studies have shown fucoidan could induce apoptosis in breast cancers, while the detailed mechanisms need to be investigated.Results of this study illustrated that number of viable MDA-MB-231 cells was decreased by fucoidan with a dose-dependent manner, while the fucoidan did not affect the viable epithelial cells number of normal human mammary (MCF10A).. After incubation with fucoidan, several apoptotic events such as chromatin condensation and increase of the population of G2/M phase were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
2
1
0
Order By: Relevance
“…The present study also detected the pathway of the fucoidan-induced apoptosis to be mitochondria-mediated, thus, confirming the LMWF-induced apoptosis to be via the activation of the intrinsic apoptosis pathway. This result is consistent with literature that the intrinsic pathway is the primary pathway in the fucoidan-induced apoptosis in the cancer cell lines [25,53].…”
Section: Resultssupporting
confidence: 93%
“…The present study also detected the pathway of the fucoidan-induced apoptosis to be mitochondria-mediated, thus, confirming the LMWF-induced apoptosis to be via the activation of the intrinsic apoptosis pathway. This result is consistent with literature that the intrinsic pathway is the primary pathway in the fucoidan-induced apoptosis in the cancer cell lines [25,53].…”
Section: Resultssupporting
confidence: 93%
“…However, the expression of XIAP in FLt + Dox treatment may regulate necroptosis [ 29 ], which needs to be confirmed in future investigations. Banafa et al showed that commercial fucoidan decreased the transcriptional expression of XIAP in MDA-MB 231 BC cells while increasing the expression of caspase 8, 3, and 9 [ 32 ]. Yang et al found that Undaria pinnatifida fucoidan downregulated XIAP expression and induced caspase 3 and 9 activation [ 33 ], as observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The total carbohydrate and uronic acid content were determined with the phenol-sulfuric acid [18] and carbazol-sulfuric acid [19] methods using L-rhamnose and D-glucuronic acid, respectively, as standards. The purified polysaccharide (70 mg) was dissolved in distilled water (20 mL) and sulfuric acid was added to reach a final concentration of 1.0 M. The mixture was subsequently heated to 100°C for 3 h. The resulting hydrolysate was neutralized with BaCO3.…”
Section: Chemical Proceduresmentioning
confidence: 99%